Nugget Tahu Formula Pury (Tafory) sebagai Alternatif Kudapan Tinggi Protein - Mahmud Aditya Rifqi; Clara M. Kusharto; Trina Astuti (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2017)
Background: Tofu nugget with pury flour is an alternative form of snack food that high in protein. Pury flour made from silkworm pupa that came from by product of silk industry. Pupa is known to have highly nutritious component specially protein that has not been optimizely used. The use of pupa flour is applicable for many form of processed food. Objective: Tofu nugget as soure of plant protein is added by pury flour to higher the protein component. Methods: This study used one factor Complete Randomized design with six levels. Level on additon pupa flour are 0%, 60%, 70%, 80%, 90% and 100% followed by organoleptic test to get chosen product. Results: The chosen product according to the test is the addition of 70% pupa flour that indicated highest best reponse by panelist. Proximate test showed that subtitution of tofu and pury flour is significanly different for water component, protein, carbohydrate, and seng. Ash elements, fat, fiber, ferum, and calcium significanlly not different. Taffory nugget contains linolenic acid. Total plate count test showed that taffory nugget is safe according to National Standard. Conclusion: It could be conclude that tafory nugget is potential as snack food with high protein.ABSTRAK Latar belakang: Tofu nugget dengan tepung Pury adalah alternatif bentuk makanan ringan yang tinggi protein. Tepung Pury terbuat dari ulat pupa yang berasal dari hasil samping industri sutra. Pupa dikenal memiliki zat gizi khususnya protein yang belum digunakan secara optimal. Penggunaan tepung pupa berlaku untuk banyak bentuk makanan olahan.Tujuan: Tofu nugget sebagai sumber protein nabati, ditambah dengan tepung Pury lebih tinggi komponen protein.Metode: Penelitian ini menggunakan desain eksperimental dengan rancangan acak lengkap dengan enam taraf. Penambahan tepung pupa adalah 0%, 60%, 70%, 80%, 90% dan 100% diikuti dengan uji organoleptik untuk mendapatkan produk yang dipilih.Hasil: Produk yang dipilih sesuai dengan uji adalah penambahan 70% tepung pupa yang ditunjukkan nilai terbaik oleh panelis. Uji proksimat menunjukkan bahwa substitusi dari tahu dan tepung pury berbeda nyata untuk komponen air, protein, karbohidrat, dan seng. Sedangkan abu, lemak, serat, zat besi dan kalsium tidak berbeda secara signifikan. Nugget Taffory mengandung asam linolenat.Kesimpulan: Dapat disimpulkan bahwa tafory nugget dapat menjadi alternatif kudapan tinggi protein bagi anak.